(untitled) - Halliday, M. A. K. (London, 1993)
The book explores the evolution of scientific discourse in the English speaking world, and the apprenticeship of students into discourse in secondary schools. A key focus is on how scientific knowledge is semiotically constructed and the ways in which students can be given access to this knowledge
Keywords: Science,Writing; Language